Análisis de la cultura organizacional en micro emprendimientos del sector Divino Niño de la ciudad de Durán - Jaime Buri, Ivette Tatiana (2022)
The environment and organizational culture must be present for the proper functioning of the organization and influence the management process of the same information and for the correct decision making, thus guaranteeing the success of business, currently the organizational climate It is a key factor that guarantees business development and prosperity. The objective of this research project was to analyze the organizational culture of micro-enterprises in the “Divino Niño” sector of the city of Durán, for which the application of surveys and interviews with businesses in the sector and with an authority were carried out, resulting in the lack of concern for having a solid organizational structure and for the lack of training on the part of the owners and relatives, in addition to the fact that in Ecuador no control institution carries out any follow-up on microentrepreneurs in order to comply with environmental regulations stipulated by law................